Labour market power and the quest for an optimal minimum wage: Evidence from Italy - Mauro Caselli; Jasmine Mondolo; Stefano Schiavo (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
This study investigates the recent trends in labour market power in Italy and assess-es the impact of a potential minimum wage using a large sample of manufacturing firms. We show that, despite an average shift of labour market power from the own-ers to the workers, monopsony power is still widespread, especially in some sectors and regions. The introduction of a minimum wage would be beneficial to workers and the economy as it reduces the monopsony power of highly productive firms paying low wages; however, it may also have a negative impact, since firms with low wages and low labour productivity may react by reducing the number of their em-ployees or even by exiting the market. Finally, we defined that an optimal minimum wage, which minimises the negative effect and maximises the positive effect for the economy, ranges between 8.25 and 9.65 euro per hour.
Keywords: J23; J38; J42; L13; 330; minimum wage; monopsony; market power; market imperfections